Genome-wide identification and expression analysis of the Hsp20, Hsp70 and Hsp90 gene family in Dendrobium officinale - Wang, Hongman; Dong, Zuqi; Chen, Jianbing; Wang, Meng; Ding, Yuting; Xue, Qingyun; Liu, Wei; Niu, Zhitao; Ding, Xiaoyu (Frontiers in Plant Science, 2022)
Dendrobium officinale, an important orchid plant with great horticultural and medicinal values, frequently suffers from abiotic or biotic stresses in the wild, which may influence its well-growth. Heat shock proteins (Hsps) play essential roles in the abiotic stress response of plants. However, they have not been systematically investigated in D. officinale. Here, we identified 37 Hsp20 genes (DenHsp20s), 43 Hsp70 genes (DenHsp70s) and 4 Hsp90 genes (DenHsp90s) in D. officinale genome. These genes were classified into 8, 4 and 2 subfamilies based on phylogenetic analysis and predicted subcellular, respectively. Sequence analysis showed that the same subfamily members have relatively conserved gene structures and similar protein motifs. Moreover, we identified 33 pairs of paralogs containing 30 pairs of tandem duplicates and 3 pairs of segmental duplicates among these genes. There were 7 pairs in DenHsp70s under positive selection, which may have important functions in helping cells withstand extreme stress. Numerous gene promoter sequences contained stress and hormone response cis-elements, especially light and MeJA response elements. Under MeJA stress, DenHsp20s, DenHsp70s and DenHsp90s responded to varying degrees, among which DenHsp20-5,6,7,16 had a strong response, which may have a strong stress resistance. Therefore, these findings could provide useful information for evolutional and functional investigations of Hsp20, Hsp70 and Hsp90 genes in D. officinale.